Synthesis of functionalized conducting polymer "polyanthranilic acid" using various oxidizing agents and formation of composites with PVC - Gupta B.; Prakash R. (My University, 2025)
Synthesis of carboxyl functionalized polyaniline (PANI) (polyanthranilic acid PANA) is reported based on our recent studies using various oxidizing agents. PANA was synthesized in acidic medium using ammonium peroxodisulfate, hydrogen peroxide, and potassium permanganate as oxidizing agents and their structural, electrochemical, and electrical properties are studied. A comparative study among the polymers formed by various oxidizing agents and also with PANI is made. Various possible oxidation states of PANA are discussed, with the help of electrochemical data. A composite of PANA and polyvinyl chloride (PVC) containing 20% PVC by weight is synthesized and used for the development of solid state pH electrode. The composite was synthesized to improve mechanical strength, stability, and restrict solubility. The pH sensor response is found to be reversible and linear in the pH range 1-7. PANA and PVC (20wt%) based pH sensors show potential applications in development of pH transducers based sensors/biosensors. © 2010 John Wiley & Sons, Ltd.